The Government Communication Mechanism in Reducing Violence Diffusion of Street Vendors Relocation Policy - Mani, La (Universitas Negeri Semarang, 2020)
This research used descriptive qualitative method. Furthermore, this study aimed to identify actors, media, models, and the nature of message design in the relocation of street vendors, so that the so that conflicts in policy communication can be reduced. Informant of this research was government apparatus of Yogyakarta. The result of the research showed that Yogyakarta government as a system in communicating the street vendors’ relocation policy involves actors who play a collaborative and integrative role of all government elements that related to the street vendors’ relocation policy. Media that is widely used is interpersonal media with participatory communication model. Message design that is informative, persuasive, mobilitative, and coercive was used simultaneously regarding the context and purpose of communication from Yogyakarta government in Indonesia.